2008
DOI: 10.1007/s11745-008-3189-y
|View full text |Cite
|
Sign up to set email alerts
|

2‐Chlorohexadecanal and 2‐Chlorohexadecanoic Acid Induce COX‐2 Expression in Human Coronary Artery Endothelial Cells

Abstract: 2-Chlorohexadecanal (2-ClHDA), a 16-carbon chain chlorinated fatty aldehyde that is produced by reactive chlorinating species attack of plasmalogens, is elevated in atherosclerotic plaques, infarcted myocardium, and activated leukocytes. We tested the hypothesis that 2-ClHDA and its metabolites, 2-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The lack of cytotoxicity described in the present study may be due to the different cell type used, as VSMCs could be more resistant to the effects of chlorohydrins than other cell types, or potential species differences. In contrast with chlorohydrins, very little is known about the actions of α-chloro fatty aldehydes as the few studies conducted focused primarily on endothelial cells and nitric oxide biosynthesis [45,46]. 2-ClHDA was thought to be an exciting prospect with its identification in atherosclerotic lesions in vivo; however, no effects were observed on the vascular remodelling processes examined in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…The lack of cytotoxicity described in the present study may be due to the different cell type used, as VSMCs could be more resistant to the effects of chlorohydrins than other cell types, or potential species differences. In contrast with chlorohydrins, very little is known about the actions of α-chloro fatty aldehydes as the few studies conducted focused primarily on endothelial cells and nitric oxide biosynthesis [45,46]. 2-ClHDA was thought to be an exciting prospect with its identification in atherosclerotic lesions in vivo; however, no effects were observed on the vascular remodelling processes examined in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown that Cl-lipids can elicit cell death in endothelial and neuronal cells, promote cell permeability leading to compromised blood-brain barrier, inhibit endothelial function by inhibiting eNOS-dependent signaling, and promote the inflammatory potential of endothelial cells, neutrophils, and macrophages (27,28,30,47,48). The precise mechanisms linking Cl-lipids to these responses remains under investigation, but modulation of MAPKs and perturbation of redox-signaling are likely candidates.…”
Section: Effects Of Cl-lipids Of Systemic Vascular Dilationmentioning
confidence: 99%
“…These rodent studies suggest that chlorin ated lipids are a component of the re sponse to bacterial and viral infection. Leukocyte-medi ated chlorinated lipid products have been shown to be biologically active species, capable of causing cardiac contractile dysfunction, NF-κB signaling in endo thelial cells, endo plasmic reticulum stress, hydrogen peroxide production, and apoptosis (38)(39)(40). Accordingly, the present study was designed to investigate the role of 2-ClFAs in human sepsis, with a focus on ARDS given evidence for the contribution of neutrophils to ARDS (20,41).…”
Section: Introductionmentioning
confidence: 99%